Fast transient solution of a two-layered counter-flow microchannel heat sink - Beh, S. L.; Tio, K. -K.; Ghulam, Abdul Quadir; Seetharamu, K. N. (Emerald Group Publishing Limited., 2010)
Link to publisher's homepage at http://www.emeraldinsight.com/